2010
DOI: 10.1021/np100484w
|View full text |Cite
|
Sign up to set email alerts
|

Dolabranes from the Chinese Mangrove, Ceriops tagal

Abstract: Six new dolabranes, named tagalsins P-U (1-6), were isolated from stems and twigs of a Chinese mangrove, Ceriops tagal, along with seven known dolabranes, an abietane, and a pimarane. The structures of these compounds were established on the basis of spectroscopic data or comparison with data in the literature. The relative configurations of tagalsins P and Q (1, 2), two new 15,16-dinor-dolabranes, were confirmed by means of single-crystal X-ray diffraction analysis. This is the first report of 16-nordolabrane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 37 publications
(49 reference statements)
1
27
0
Order By: Relevance
“…In addition, it is reported that the crude extract of the plant possesses the activities to cure for hepatitis and diabetes [10]. Previous chemical investigation revealed that C. tagal not only abounded in tannins and triterpenoids [11,12], but also contained diverse dolabrane-type diterpenes such as tagalsin A-U [13][14][15] and tetraterpens [16,17]. Terpenoids from the root of C. tagal possess antifouling activity, while dolabrane derivatives exerted antifeedant and anticancer activities.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is reported that the crude extract of the plant possesses the activities to cure for hepatitis and diabetes [10]. Previous chemical investigation revealed that C. tagal not only abounded in tannins and triterpenoids [11,12], but also contained diverse dolabrane-type diterpenes such as tagalsin A-U [13][14][15] and tetraterpens [16,17]. Terpenoids from the root of C. tagal possess antifouling activity, while dolabrane derivatives exerted antifeedant and anticancer activities.…”
Section: Introductionmentioning
confidence: 99%
“…The relative configurations of tagalsins P and Q (9 and 12, resp.) were confirmed by means of single-crystal X-ray diffraction analysis in 2010 [10]. Tagalsins A -G and O (1 -7 and 8, resp.)…”
mentioning
confidence: 76%
“…Compounds 12, 14, and 17, obtained from stems and twigs of the Chinese C. tagal, exhibited moderate antifeedant activity against the third-instar larvae of Brontispa longissima at a concentration of 1 mg ml À 1 . However, Compounds 12 -17 showed no significant activities against human melanoma (A2058, G361), prostate (DU145), and breast (MDA-MB-468, MDA-MB-435) cancer cell lines [10].…”
mentioning
confidence: 98%
“…For ring conformations, see: Cremer & Pople (1975). For background to diterpenoids, see, for example: Hu et al (2010); Zhang et al (2005). For related structures, see: Chantrapromma et al (2007); Fun et al (2006).…”
Section: Related Literaturementioning
confidence: 99%